PENGARUH KEBIASAAN MEMBACA DAN PENGUASAAN TATA BAHASA TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPTIF BAHASA INGGRIS - Cicilia Nanik Kurniawati; Gustaman Saragih; Soenardjati Djajanegara (Universitas Indraprasta PGRI, 2020)
The purpose of this study is to determine the effect of reading habit and grammar mastery towards the Students descriptive writing, then do research using the survey method. The sample used 90 students with cluster random sampling technique. The results showed that there is a significant influence reading habits and mastery of grammar together on the ability to write descriptive texts English. This is evidenced by the acquisition of the Sig. 0.000 <0.05 and Fh = 18.414. Together. 2) There is a significant effect on the ability of the habit of reading English writing descriptive texts. This is evidenced by the acquisition of the Sig 0,002, <0.05 and th =3,235. 3). Also, there is a significant effect on the ability of mastering grammar writing descriptive texts English. This is evidenced by the acquisition Sig.0,005 value <0.05 and th =2902Keywords: reading habits; grammar mastery; foreign language writing; descriptive text.